PEMANFAATAN KECERDASAN BUATAN (AI) UNTUK MENDUKUNG KEMANDIRAN BELAJAR SISWA - Beatricia; Hannes Magdalena Hutagalung; Esrawati Satriana Simanullang; Jessica Callista; Jocerenn Laurence (Universitas Negeri Surabaya, 2026)
One of the most influential technologies in today's education world is Artificial Intelligence (AI). Students often use AI as an alternative to find out what they need. Furthermore, students often rely on AI to complete their assignments. The purpose of this study was to determine the level of student learning independence when utilizing AI while studying. The research method used was quantitative with a descriptive approach. The study took place at SMA Wiyata Dharma Medan, with a population of 245 students and a sample of 40 students. Data collection used questionnaires and document studies. The results showed that AI has positive benefits and a very high contribution to increasing student learning independence, with a score reaching 84.2%. This score indicates students' frequent use of AI to search for new materials, relevant references, complete assignments well and on time, and understand the subject matter. This positive use of AI indicates that SMA Wiyata Dharma Medan students have a high level of initiative in learning and motivation to learn independently in a disciplined manner. This learning independence is a sign that SMA Wiyata Dharma Medan students are capable of self-management, making decisions, and taking responsibility for themselves.